2015
DOI: 10.2110/jsr.2015.29
|View full text |Cite
|
Sign up to set email alerts
|

Paleohydrology and 3D Facies Architecture of Ancient Point Bars, Ferron Sandstone, Notom Delta, South-Central Utah, U.S.A

Abstract: Most outcrops of fluvial deposits consist of a series of cliff exposures, either natural or manmade (e.g., roadcuts). Predictions, and especially observation of plan-form geometry, such as might be made with numerical experiments or from studies of modern rivers, are challenging to test in most ancient outcrops. This study examines ancient exhumed channel belts from the Cretaceous Notom Delta of the Ferron Sandstone Member in south-central Utah. Extensive plan-view exposures with local vertical cliff exposures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 64 publications
1
22
1
Order By: Relevance
“…An independent check on this figure was provided by relating cross‐set data to dune height and hence formative flow depth (Bridge & Tye, ; Leclair & Bridge, ; Wu et al ., ). This was feasible because the standard deviation to mean thickness ratio of the cross‐sets was approximately equal to 0·88(±0·3) (Bridge & Tye, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An independent check on this figure was provided by relating cross‐set data to dune height and hence formative flow depth (Bridge & Tye, ; Leclair & Bridge, ; Wu et al ., ). This was feasible because the standard deviation to mean thickness ratio of the cross‐sets was approximately equal to 0·88(±0·3) (Bridge & Tye, ).…”
Section: Discussionmentioning
confidence: 99%
“…Palaeocurrent data were collected to determine local palaeotransport directions, whilst dune cross‐set thicknesses were collected for the purpose of calculating dune heights and hence formative flow depths (cf. Bridge & Tye, ; Leclair & Bridge, ; Wu et al ., ). Dip azimuth data for internal depositional surfaces were also collected.…”
Section: Study Site and Methodologymentioning
confidence: 97%
“…At dune-scale, the bidirectionality could be tidal or an apparent feature due to 2D exposure of trough cross-bedding or of the fluvial bar. For example, detailed work from the Ferron Sandstone in Utah, USA (Wu et al, 2015), indicated a high spread of palaeocurrents that was explained by the stacking pattern of point-bar deposits, and probably purely fluvial conditions. Am4: heterolithic deposits Heterolithic deposits (Fig.…”
Section: Amber: Ambiguous Fluvial or Tidal Featuresmentioning
confidence: 99%
“…Point bars with ‘ridge and swale’ topography are traditionally thought to be common features in meandering rivers (Gibling & Rust, ), whereas amalgamated compound point bars are increasingly recognized as important architectural components in low sinuosity, meandering or braided rivers (Lunt & Bridge, ; Moody & Meade, ; Wu et al ., ). Despite having a distinct facies architecture, formative sinuous channels associated with point bars show migration patterns ranging from lateral expansion to downstream translation in a number of modern (Hickin, ) and ancient examples (Wu et al ., ) and in several flume and theoretical studies (Peakall et al ., ; Duan & Julien, ). Moreover, recent flume studies (van de Lageweg et al ., ) and theoretical models (Eke et al ., ) show that the deposition of point bars in meandering rivers could be a passive response of bank retreat (also known as ‘bank pull’).…”
Section: Introductionmentioning
confidence: 97%
“…Flow processes associated with different types of point bars have rarely been documented in ancient fluvial deposits, because along‐stream changes of bar characteristics are difficult to document in two‐dimensional (2D) outcrops and their plan‐view forms must be extrapolated. Despite an increased focus on plan‐view macroform geometry in ancient outcrops (Brooks, ; Foix et al ., ; Ielpi & Ghinassi, ; Bhattacharyya et al ., ; Wu et al ., ), the signatures of flow processes preserved in the rock record have rarely been investigated.…”
Section: Introductionmentioning
confidence: 99%